An experimental evidence of the squirt-flow effect in glycerol-saturated berea sandstone at seismic frequencies - Mikhaltsevitch, Vassili; Lebedev, Maxim; Gurevich, Boris (2016)
In sedimentary rocks saturated with fluid characterized by low mobility, which can be determined by low intrinsic permeability or high fluid viscosity, relative motion between pore fluid and rock skeleton may produce a significant impact on acoustic wave attenuation and dispersion of the elastic moduli of rocks at seismic frequencies. To investigate the influence of low-mobility pore fluid on elastic and anelastic parameters of sedimentary rock, the seismic-frequency laboratory measurements on dry and glycerol saturated Berea sandstone were carried out. The elastic moduli and extensional attenuation of the sandstone were measured at differential pressures of 5 MPa and 10 MPa under temperatures of 23 and 31 ° C. Noticeable peaks of attenuation and significant dispersion of the moduli were detected for the glycerol-saturated sample. It was found that the frequencies of the peaks increase approximately twofold when the viscosity of glycerol was reduced by half with the temperature changing from 23 °C to 31 °C. Our analysis shows that the quantitative relationship between the extensional attenuation and the Young's modulus measured for the glycerol-saturated sandstone is consistent with the causality principle presented by the Kramers-Kronig relationship.